Influence of leaf removal on berry thermal efficiency for anthocyanin accumulation - Gouveia, João (2015)
The aim of this work was to analyse the effects of leaf removal on Touriga Nacional berry temperature and consequent thermal efficiency for anthocyanins biosynthesis. The field experiment was located at Dão Wine Research Station, Nelas, Portugal in an adult vineyard planted with North-South oriented rows, with the red grape variety Touriga Nacional grafted on 110R rootstock. The vines were trained on a vertical shoot positioning, spur-pruned on a bilateral Royat cordon system and deficit irrigated (50% ETc). The experimental design was a randomized complete block design with four replications of twelve vines per elemental plot, and the following two treatments: basal leaf removal (LR) and a control non-defoliated (ND). Berry temperature (Tb) was measured continuously during the second half (3rd to 19th September) of the 2009 ripening period using two-junction, fine-wires copper-constantan thermocouples manually inserted into the berries and connected to a data logger. A sample of clusters located in different canopy positions (exposed and internal; facing East and West) of 4 vines per treatment were used. To quantify the effect of Tb on anthocyanins biosynthesis, the berry hourly mean temperatures were converted into normal heat hours (NHH) and accumulated per day (NHHd) and per monitoring period (NHHc). For quantification of thermal requirements for anthocyanins synthesis and accumulation, a minimum of 10°C, a maximum of 35°C, and an optimum of 26°C were used. Meteorological variables were measured at an automatic weather station installed within the experimental plot. For all days of the monitoring period, daily average berry temperature (dTb) of all monitored berries was lower in ND treatment than in LR, being the maximum differences between treatments registered on 11th September. The highest dTb differences between treatments were registered on the clusters located at the west side of the canopy on 7th September while dTb of the clusters located in the centre of the canopy was less affected by leaf removal. The control non-defoliated treatment (ND) presented a significantly higher NHHc than that of LR being the higher differences presented by the clusters located in the west side. The lowest differences in NHHc were obtained in the clusters located in the centre of the canopy. Our results show that the thermal efficiency for berry anthocyanins accumulation was significantly affected by leaf removal and that this effect was dependent of the meteorological conditions, time of the day and berry/cluster location into the vine canopy.